2009
DOI: 10.1007/s11127-009-9558-0
|View full text |Cite
|
Sign up to set email alerts
|

A positive theory of the earnings relationship of unemployment benefits

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Government ideology does not turn out to be statistically significant. This result is thus not in line with Goerke et al (2010), who found significant ideology effects. Possible explanations for this discrepancy are that Goerke et al (2010) estimate their model in levels while I employ growth rates, that they consider a longer observation period, and that their dependent variables is a broader measure of unemployment compensation.…”
Section: Replacement Ratecontrasting
confidence: 78%
See 1 more Smart Citation
“…Government ideology does not turn out to be statistically significant. This result is thus not in line with Goerke et al (2010), who found significant ideology effects. Possible explanations for this discrepancy are that Goerke et al (2010) estimate their model in levels while I employ growth rates, that they consider a longer observation period, and that their dependent variables is a broader measure of unemployment compensation.…”
Section: Replacement Ratecontrasting
confidence: 78%
“…One group of political economic models focuses on the determinants of unemployment benefits, and, thus explains the replacement rate and the benefit length. Goerke et al (2010) The regression results in Table 1 illustrate that unemployment replacement rates were highly persistent over time: the lagged dependent variable is statistically significant at the 1% level and corroborates a point estimate of around 0.16. Moreover, an "F-Test" on the joint insignificance of the fixed period effects can be strongly rejected.…”
Section: Replacement Ratementioning
confidence: 53%
“…it maximizes its members' gain from employment over unemployment (or any other alternative income). The extent to which unions pursue given objectives remains an open empirical question (see Booth, 1995b;Goerke et al, 2007;Oswald, 1982Oswald, , 1993Pencavel, 1991). I assume, partly following Goerke et al (2007), that the union maximizes the gain from employment over unemployment, i.e.…”
Section: The Modelmentioning
confidence: 99%
“…Or the union can be insider-dominated, maximizing the gain of its members from employment over unemployment. It remains an open empirical question which objective is pursued (see GOERKE, PANNENBERG, AND URSPRUNG [2007], BOOTH [1995], PENCAVEL [1991], andOSWALD [1982], [1993]). Following STÄHLER [2008], we assume that the union solely maximizes the gain from employment over unemployment, which is close to the formulation of OSWALD [1993].…”
Section: The Basic Model and Equilibriummentioning
confidence: 99%